2013
DOI: 10.1590/s0100-06832013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Processo de formação de crostas superficiais em razão de sistemas de preparo do solo e chuva simulada

Abstract: A chuva provoca a modificação da estrutura superficial do solo levando ao desenvolvimento de crostas. Este estudo avaliou a dinâmica da formação de crostas superficiais por meio da análise e descrição micromorfológica de lâminas delgadas. O experimento foi conduzido em 2009 e 2010. Em parcelas de 15 x 30 m, foram implantados os diferentes sistemas de preparos do solo: preparo convencional (PC), preparo reduzido (PR) e sem preparo (SP). Dentro das parcelas instalaramse as microparcelas de 1 x 1m e aplicaram-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…Soil crusting was visually observed by the authors during the experimental period, but was not quantified. Several studies confirm the occurrence of sealing and crusting of the surface by the action of rain and/or runoff under various management conditions, especially on bare soil (Reichert et al, 1994;Reichert and Norton, 1995;Lado et al, 2004;Le Bissonnais et al, 2005;Rosa et al, 2013).…”
Section: Losses Of Water and Soil Through Erosionmentioning
confidence: 83%
“…Soil crusting was visually observed by the authors during the experimental period, but was not quantified. Several studies confirm the occurrence of sealing and crusting of the surface by the action of rain and/or runoff under various management conditions, especially on bare soil (Reichert et al, 1994;Reichert and Norton, 1995;Lado et al, 2004;Le Bissonnais et al, 2005;Rosa et al, 2013).…”
Section: Losses Of Water and Soil Through Erosionmentioning
confidence: 83%
“…Studies have recommended the adoption of soil conservation systems, such as reduced or no-tillage, to prevent soil structural degradation, crust formation and soil loss by erosion [23][24][25][26]. Part of this study has already been published and showed that the greater soil revolving and incorporation of crop residues, promotes greater degradation by drop impact and crust formation [27]. However, many aspects about the process dynamics of crust formation in these tillage systems still need clarification, such as the changes caused by rain events on the surface porosity and the predominant pore types.…”
Section: Introductionmentioning
confidence: 88%
“…The rainfall was applied to an area corresponding to 1 m 2 . Studies using rainfall simulators are frequently used to evaluate surface degradation and crust formation [27], aggregate breakdown [22,31] and soil erosion [32].…”
Section: First Year Of Experiments (2009)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dalla Rosa et al (2013), the application of rain on turned-over soil without cover causes degradation of the surface structure, which, afterwards, is reorganized and oriented at the surface. This is related to the low stability of the soil aggregates cultivated under this system, which is caused by the reduction in biological quality of the soil (Aziz et al, 2013) and by the effect of the increased number of diskings, which lead to break up of the surface layer of the soil.…”
Section: Effect Of Rain On Surface Roughnessmentioning
confidence: 99%